Detecting faces in specific scenarios: Systematic Literature Review - Dias, Bruno Gonçalves; Ivamoto, Victor Soares; Lima, Clodoaldo Aparecido de Moraes (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2023: Anais do XX Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2023.234273, 2023)
Facial detection is a base component for multiple applications in the fields of biometrics, surveillance, human-robot interaction and others. Although significant progress has been made in the field over the past decade, there are still gaps to be addressed, particularly in specific scenarios as the presence of partial occlusion, variations of lighting, pose, and scale among others. This work aims to provide a comprehensive evaluation of recent studies on facial detection in the wild through a systematic literature review. The review includes a focus on the use of scenario-specific information within the field. A total of forty-five papers were analyzed to provide an overview of the field, incorporating information on scenarios.